Evaluación de cepas de Rhizobium en diferentes ecotipos de maní (Arachis hypaea) (1997)
in the Valle del Alto Magdalena there an about 2000 hectares grown with groundnut. There is a particular interest for Urea utilization through Rhizobium sp stumps. An experiment was carried out in the area of Mariquita (Tolima) on a loamy sand soil, at 314 m.a.s.l. with 2200 mm of annual raingail, overage temperature of 26C and Relative humidity of 77%: the main objective of the study was to determine the effect of three (3) stumps of Rhizobium sp CORPOICA, compared with a control and a control plus 100 kg of Nitrogen per hectare, on the production of thee (3) growndnut varieties (Tatui 76, - Florunner and Oira). It was used and experimental design of completely randomized blocks. Rhizobiurn stumps evaluated did not show any possitive effect on yield, (1176.7 kg/ha) when compared with the absolute control and the control plus 100 kg N/ha (1172.5 kg/ ha) which means that the stumps evaluated are not efficient fot this zone. There was not specifity among the stumps and the varieties of growndnut evaluated. The results suggest that for the North of Tolima, growndnut becomes easily in simbiosis with native stumps of Rhizobium which are present in the soil, i.e., varieties such as Tatul 76, Florunner and Oira do not need to be inoculated to become in association with the bacter.